High-intensity interval training programs and their impact on endurance performance in handball players: a systematic review - Henrique, Jos? Rocha (2024)
Study aim: This systematic review aimed to identify and analyze the available evidence about the effects of high-intensity interval training (HIIT) interventions on endurance performance in handball players. Material and methods: The search for relevant literature was conducted across prominent databases, including PubMed, Scopus, SPORTDiscus, and Web of Science Core Collection. The eligibility criteria focused on healthy handball players, without restrictions on age, sex, or competitive level, who were exposed to HIIT interventions, either alone or in combination with other training methods. The methodological assessment employed the RoB2 and ROBINS scales. A screening process was executed, evaluating 434 titles, leading to the inclusion of 17 eligible studies in this systematic review, comprising a total of 369 participants. Results: Most studies on HIIT in handball involved tier-two athletes (trained/developmental) and mostly men. The training frequency typically implemented was twice per week, with a duration between 4 and 12 weeks, with different types of HIIT. There was considerable variation in outcomes across the included studies, with most of them demonstrating a significant positive impact of HIIT on improving endurance performance when compared to controls. Conclusion: In conclusion, the predominant focus of the overall analyzed studies was on the effects of different HIIT interventions in obtaining positive performance adaptations assessed by field-based tests in handball players.